Impact of Hard Skills, Soft Skills and Organizational Culture: Lecturer Innovation Competencies as Mediating - Masduki Asbari; Agus Purwanto; Freddy Ong; Anggaripeni Mustikasiwi; Siti Maesaroh; Mustofa Mustofa; Dhaniel Hutagalung; Yulia Andriyani (Universitas Muhammadiyah Enrekang, 2020)
This study aims to measure the effect of hard skills and soft skills on the innovation ability of private university lecturers in Jabodetabek mediated by organizational culture. Data collection is done by simple random sampling via electronic to the population of private university lecturers in Jabodetabek. The returned and valid questionnaire results are 513 samples. Data processing using SEM method with SmartPLS 3.0 software. The results of this study concluded that hard skills and soft skills have a positive and significant effect on the ability of lecturers' innovation, both directly and indirectly through organizational culture mediation This new research proposes a model to build the ability of lecturer innovation among the lecturers of private tertiary institutions in Jabodetabek through enhancing hard skills and soft skills with organizational culture as a mediator. This research can pave the way to improve the readiness of lecturers in facing the 4.0 education era.